Religion and Early Marriage in the United States: Evidence from the Add Health Study - Uecker, Jeremy (2014)
Early marriage has important consequences for individuals in the United States. Several studies have linked religion to early marriage but have not examined this relationship in depth. Using data from Waves 1, 3, and 4 of the National Longitudinal Study of Adolescent Health, I conduct multilevel event-history analysis to examine how religion, at both individual and contextual levels, is associated with early marriage. Further, I test mediators of the religion-early marriage relationship. I find significant variation in early marriage by religious tradition, religious service attendance, religious salience, belief in scriptural inerrancy, and religious context in high school. The individual religious effects—but not the school context effects—are explained in part by differential attitudes toward marriage and cohabitation.